Silver rich mineral paper processing method and silver rich mineral paper

By plating aluminum on stone paper and coating it with polyurethane resin and water-based paint layers to form a laser pattern, the problems of poor aesthetics and printing adaptability of stone paper were solved, achieving the effects of good aesthetics, excellent anti-air permeability and strong printing adaptability.

CN120756125APending Publication Date: 2025-10-10HUNAN HERUI LASER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510917037.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-03
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing stone paper has poor aesthetics, insufficient airtightness, and poor printing adaptability, resulting in low usage.

Method used

A continuous, bright aluminum layer is added to the stone paper, and polyurethane resin and water-based paint layers are coated on the aluminum layer to form an embossed layer with a laser pattern. The aluminum layer improves the aesthetics, and the polyurethane resin layer increases the adhesion of the printing ink and improves the printing adaptability.

Benefits of technology

The aesthetics and airtightness of stone paper are improved, the printing adaptability is enhanced, and the printing effect is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120756125A_ABST
    Figure CN120756125A_ABST
Patent Text Reader

Abstract

The invention specifically discloses a silver rich mineral paper processing method and silver rich mineral paper. The method comprises the following steps: S100, preparing a transparent transfer film: sequentially coating a base film with a water-based coating layer and a polyurethane resin layer; s200, aluminum is plated on the surface of the prepared transparent transfer film to form a continuous and bright metal aluminum layer, and a silver transfer film is obtained; s300, coating glue on the surface of the metal aluminum layer of the silver transfer film to form a glue layer; s400, the stone body paper is attached to the glue layer on the silver transfer film, and silver stone paper with the transfer film is obtained; and S500, stripping the base film on the silver rich mineral paper with the transfer film to obtain the silver rich mineral paper. According to the processing method provided by the invention, the aesthetic degree of the rich mineral paper is remarkably improved, meanwhile, the waterproof performance of the rich mineral paper is also improved, the air permeability of the rich mineral paper is also reduced, and the printing adaptability of the rich mineral paper is thoroughly changed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of stone paper, and in particular to a silver stone paper processing method and the silver stone paper. Background Art

[0002] Stone paper is a new material between paper and plastic, capable of replacing both some traditional paper and most traditional plastic packaging. Its low cost and biodegradability offer significant cost savings and are pollution-free. As a replacement for traditional paper, it can conserve forest resources and reduce secondary pollution generated during the papermaking process. As a replacement for plastic packaging, it can conserve petroleum resources and degrade after use, contributing to environmental protection. However, existing stone paper suffers from poor aesthetics, inferior air permeability compared to plastic, poor printing adaptability, unstable printed content, and difficulty achieving optimal post-press processing, leading to limited usage. Summary of the Invention

[0003] The object of the present invention is to provide a method for processing silver stone paper, the method comprising the following steps:

[0004] S100, preparing a transparent transfer film: coating a water-based coating layer and a polyurethane resin layer on the base film in sequence;

[0005] S200, plating aluminum on the surface of the prepared transparent transfer film to form a continuous bright metal aluminum layer to obtain a silver transfer film;

[0006] S300, applying glue on the surface of the metal aluminum layer of the silver transfer film to form a glue layer;

[0007] S400, laminating the stone base paper to the glue layer on the silver transfer film to obtain the silver stone paper with the transfer film;

[0008] S500: Peeling off the base film on the silver stone paper with the transfer film to obtain the silver stone paper.

[0009] In some embodiments, in step S100, the base film is a PET base film, the base film thickness is 12-14 microns, and the base film surface tension is greater than 46 dynes; and / or

[0010] The thickness of the water-based coating layer is 1-1.3 microns, and the solid content of the water-based coating layer is 18-22%; and / or

[0011] The thickness of the polyurethane resin layer is 1.7-2.2 microns, and the solid content of the polyurethane resin layer is 28-32%.

[0012] In some embodiments, the water-based coating used in the water-based coating layer includes the following components in weight percentage:

[0013]

[0014]

[0015] In some embodiments, the mixed solvent is a mixed solution of water and anhydrous ethanol in a volume ratio of 2-4:7.

[0016] In some embodiments, the method further includes step S100 ′: performing laser embossing on the transparent polyurethane resin layer on the base film, thereby forming an embossed layer having a laser pattern on the polyurethane resin layer.

[0017] In some embodiments, step S200 is specifically as follows: placing the transparent transfer film into an aluminum plating machine, and using the aluminum plating machine to plate aluminum on the surface of the polyurethane resin layer or the embossed layer, thereby forming a continuous bright or laser-effect metal aluminum layer to obtain a silver transfer film.

[0018] In some embodiments, the step S300 is specifically as follows: applying glue on the surface of the metal aluminum layer of the silver transfer film by a glue roller to form a glue layer, and using an oven to dry the diluent in the glue layer, wherein the oven is an oven with five sections with different temperatures, the temperature of the first section oven is 60-65°C, the temperature of the second section oven is 70-75°C, the temperature of the third section oven is 80-85°C, the temperature of the fourth section oven is 90-95°C, and the temperature of the fifth section oven is 90-85°C.

[0019] In some embodiments, step 400 is specifically as follows: preheating the silver transfer film drawn out of the oven to 70±2°C, and then laminating the stone base paper and the silver transfer film on a laminating roller through the glue layer on the silver transfer film, wherein the laminating speed is 88-92m / min, the pressure of the laminating roller is 0.4Mpa-0.6Mpa, the laminating roller includes an upper roller and a lower roller, the upper roller is a PU roller with a Shore A of 85-90 degrees, the center height of the upper roller is 0.2-0.3mm, the lower roller is a hollow oil-warmed roller, and the oil temperature of the lower roller is 75±2°C.

[0020] In some embodiments, step S400' is further included: rolling the silver stone paper with the transfer film into a roll and curing it at a first preset temperature for 48-72 hours, wherein the rolling tension is 20±2 kg and the first preset temperature is 45-55°C.

[0021] The present application also provides a silver stone paper, which is made according to the above-mentioned processing method.

[0022] Compared to the prior art, the present invention provides a silver stone paper processing method and silver stone paper. This processing method improves the aesthetics of the stone paper while also reducing its air permeability by adding a continuous, bright aluminum coating layer to the stone paper. Furthermore, the polyurethane resin layer and water-based coating layer applied to the aluminum coating layer enhance the adhesion of the stone paper to printing ink, thereby improving the stone paper's printability and post-processing performance. Furthermore, by forming an embossed layer with a laser pattern on the polyurethane resin layer, the aesthetics of the stone paper are further enhanced. Therefore, compared to the prior art, the silver stone paper produced by the silver stone paper processing method provided in this application has the characteristics of good aesthetics, superior air permeability, and strong printability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a flow chart of a silver stone paper processing method according to an embodiment of the present application.

[0024] Figure 2 Schematic diagram of the structure of the transparent transfer film in the embodiment of the present application.

[0025] Figure 3 This is a schematic diagram of the structure of the silver stone paper in the embodiment of this application.

[0026] Figure 4 is a schematic diagram of the stone backing paper in this application,

[0027] Figure 5 is a schematic diagram of silver stone paper prepared in some embodiments of this application,

[0028] Figure 6 Schematic diagram of the laser silver stone paper prepared in some embodiments of the present application.

[0029] In the figure: 1. Base film, 2. Water-based paint layer, 3. Polyurethane resin layer, 4. Embossed layer, 5. Aluminum coating layer, 6. Glue layer, 7. Stone backing paper. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.

[0031] like Figure 1-Figure 3 As shown, this embodiment provides a method for processing silver stone paper, which includes the following steps:

[0032] S100, preparing a transparent transfer film: coating a water-based coating layer and a polyurethane resin layer on the base film in sequence;

[0033] In this step, the base film is a PET base film with a thickness of 12-14 microns and a surface tension greater than 46 dynes; the thickness of the water-based coating layer is 1-1.3 microns, and the solid content of the water-based coating layer is 18-22%; the thickness of the polyurethane resin layer is 1.7-2.2 microns, and the solid content of the polyurethane resin layer is 28-32%. The water-based coating used in the water-based coating layer includes the following components in weight percentage:

[0034]

[0035] The mixed solvent is a mixed solution of water and anhydrous ethanol in a volume ratio of 2-4:7.

[0036] And / or, the method further includes step S100': performing laser embossing on the transparent polyurethane resin layer on the base film to form an embossed layer with a laser pattern on the polyurethane resin layer, and then rolling the embossed layer to complete the production of the transparent transfer film.

[0037] S200, plating aluminum on the surface of the prepared transparent transfer film to form a continuous bright metal aluminum layer to obtain a silver transfer film;

[0038] This step is specifically as follows: placing the transparent transfer film into an aluminizing machine, using the aluminizing machine to plate aluminum on the surface of the polyurethane resin layer or the embossed layer, thereby forming a continuous bright or laser-effect metal aluminum layer to obtain a silver transfer film. The silver transfer film can then be cut into the required specifications according to actual needs and then rolled up.

[0039] S300, applying glue on the surface of the metal aluminum layer of the silver transfer film to form a glue layer;

[0040] This step is specifically as follows: glue is applied to the surface of the metal aluminum layer of the silver transfer film by a glue roller to form a glue layer, and the diluent in the glue layer is dried in an oven, wherein the oven has five sections with different temperatures, the temperature of the first section is 60-65°C, the temperature of the second section is 70-75°C, the temperature of the third section is 80-85°C, the temperature of the fourth section is 90-95°C, and the temperature of the fifth section is 90-85°C.

[0041] S400, laminating the stone base paper to the glue layer on the silver transfer film to obtain the silver stone paper with the transfer film;

[0042] This step is specifically as follows: preheating the silver transfer film drawn out of the oven to 70±2°C, and then laminating the stone backing paper and the silver transfer film on the laminating roller through the glue layer on the silver transfer film, wherein the laminating speed is 88-92m / min, the pressure of the laminating roller is 0.4Mpa-0.6Mpa, and the laminating roller includes an upper roller and a lower roller. The upper roller is a PU roller with a Shore A of 85-90 degrees and a center height of 0.2-0.3mm. The lower roller is a hollow oil-warmed roller, and the oil temperature of the lower roller is 75±2 degrees.

[0043] And / or, further comprising step S400': rolling the silver stone paper with the transfer film into a roll, and curing it at a first preset temperature for 48-72 hours, wherein the rolling tension is 20±2 kg and the first preset temperature is 45-55°C.

[0044] S500: Peeling off the base film on the silver stone paper with the transfer film to obtain the silver stone paper.

[0045] In the above embodiment, a continuous, bright aluminum layer is added to the stone paper. This aluminum layer not only improves the aesthetics of the stone paper but also reduces its air permeability. A polyurethane resin layer and a water-based coating layer are simultaneously applied to the aluminum layer. The water-based coating layer enhances the adhesion of the stone paper to printing ink, thereby improving its printability and post-processing performance. Furthermore, an embossed layer with a laser pattern is formed on the polyurethane resin layer, further enhancing the aesthetics of the stone paper. Therefore, compared to the prior art, the silver stone paper produced by the silver stone paper processing method provided in this application has the characteristics of good aesthetics, superior air permeability, and strong printability.

[0046] The present application also provides a silver stone paper, which is produced based on the above-mentioned processing method.

[0047] Based on the description of the beneficial technical effects of the processing method described above, the silver stone paper produced according to the processing method has the same beneficial technical effects, which will not be repeated here.

[0048] In order to further illustrate the working principle and beneficial effects of the present application, the waterproof performance and air permeability of commercially available stone paper and the silver stone paper prepared by the processing method provided in the present application were tested simultaneously. The test results are shown in Table 1.

[0049] In this embodiment, the Cobb value test method is used to test the waterproof performance of the test paper sample. The specific steps are as follows: 2Fix the test paper sample with a metal ring or cup, inject 100 ml of distilled water, pour out the distilled water after 12 hours and absorb the residual water on the surface of the test paper sample. Weigh the test paper sample before and after water absorption, and then calculate the Cobb value of the test paper sample. The calculation formula is Cobb value = (weight of test paper sample after water absorption - weight of test paper sample before water absorption) * 100.

[0050] In this embodiment, the Gurley method is used to test the air permeability of the test paper sample. The specific steps are as follows: select an effective area of ​​6.42 cm 2 Use a test paper sample (corresponding to a fixture aperture of Φ28.6mm, a test paper sample size of 50mm×50mm, and the test paper sample must be free of defects such as wrinkles and cracks) and record the time required for 100ml of air to vertically pass through the test paper sample under a certain pressure difference of 1.23kPa.

[0051] Table 1 Performance test results of commercially available stone paper and the silver stone paper prepared in this application

[0052]

[0053] from Figure 4-Figure 6 It can be seen that Figure 4 Compared with the stone-based paper (commercially available stone paper), the silver stone paper and the laser silver stone paper prepared in this application have better aesthetics.

[0054] As can be seen from Table 1, the Cobb value of the silver stone paper prepared in this application is 0.05 g / m 2 The time required for 100ml of air to vertically penetrate the silver stone paper is 10000s, while the Cobb value of commercially available stone paper is 7.5g / m 2 The time required for 100 ml of air to vertically pass through the silver stone paper is 4000 s. It can be seen that the waterproof and breathable properties of the silver stone paper prepared in this application are better than those of commercially available stone paper.

[0055] As can be seen from Table 1, the Cobb value of the laser silver stone paper prepared in this application is 0.06 g / m 2 The time required for 100ml of air to vertically pass through the silver stone paper is 9800s, while the Cobb value of commercially available stone paper is 7.5g / m 2 The time required for 100 ml of air to vertically pass through the silver stone paper is 4000 s. It can be seen that the waterproof and breathable properties of the laser silver stone paper prepared in this application are better than those of commercially available stone paper.

[0056] In summary, compared with the prior art, the silver stone paper produced by the processing method provided in this application effectively improves the waterproof performance of the stone paper while also reducing its air permeability, thereby changing the stone paper's printability and post-processing performance. Furthermore, this application also significantly improves the stone paper's aesthetics. The silver stone paper produced by the silver stone paper processing method provided in this application has the characteristics of good aesthetics, superior air permeability, and strong printability.

[0057] The above describes in detail the silver stone paper processing method and silver stone paper provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The above examples are merely intended to facilitate understanding of the core concepts of the present invention. It should be noted that those skilled in the art will be able to make various improvements and modifications to the present invention without departing from the principles of the present invention, and such improvements and modifications fall within the scope of protection of the claims.

Claims

1. A method for processing silver stone paper, characterized in that: The method comprises the following steps: S100, preparing a transparent transfer film: coating a water-based coating layer and a polyurethane resin layer on the base film in sequence; S200, plating aluminum on the surface of the prepared transparent transfer film to form a continuous bright metal aluminum layer to obtain a silver transfer film; S300, applying glue on the surface of the metal aluminum layer of the silver transfer film to form a glue layer; S400, laminating the stone base paper to the glue layer on the silver transfer film to obtain the silver stone paper with the transfer film; S500: Peeling off the base film on the silver stone paper with the transfer film to obtain the silver stone paper.

2. The processing method according to claim 1, characterized in that: In step S100, the base film is a PET base film, the base film thickness is 12-14 microns, and the base film surface tension is greater than 46 dynes; and / or The thickness of the water-based coating layer is 1-1.3 microns, and the solid content of the water-based coating layer is 18-22%; and / or The thickness of the polyurethane resin layer is 1.7-2.2 microns, and the solid content of the polyurethane resin layer is 28-32%.

3. The processing method according to claim 2, characterized in that: The water-based coating used in the water-based coating layer includes the following components in weight percentage:

4. The processing method according to claim 3, characterized in that: The mixed solvent is a mixed solution of water and anhydrous ethanol in a volume ratio of 2-4:

7.

5. The processing method according to claim 4, characterized in that: The method further includes step S100 ′: performing laser embossing on the transparent polyurethane resin layer on the base film, thereby forming an embossed layer with a laser pattern on the polyurethane resin layer.

6. The processing method according to claim 4 or 5, characterized in that: The step S200 specifically includes: placing the transparent transfer film into an aluminum plating machine, and using the aluminum plating machine to plate aluminum on the surface of the polyurethane resin layer or the embossed layer, thereby forming a continuous bright or laser-effect metal aluminum layer to obtain a silver transfer film.

7. The processing method according to claim 6, characterized in that: The step S300 specifically comprises: applying glue on the surface of the metal aluminum layer of the silver transfer film by a glue roller to form a glue layer, and using an oven to dry the diluent in the glue layer, wherein the oven is a five-section oven with different temperatures, the temperature of the first section oven is 60-65°C, the temperature of the second section oven is 70-75°C, the temperature of the third section oven is 80-85°C, the temperature of the fourth section oven is 90-95°C, and the temperature of the fifth section oven is 90-85°C.

8. The processing method according to claim 7, characterized in that: The step 400 is specifically as follows: preheating the silver transfer film drawn out from the oven to 70±2°C, and then laminating the stone backing paper and the silver transfer film on a laminating roller through the glue layer on the silver transfer film, wherein the laminating speed is 88-92m / min, the pressure of the laminating roller is 0.4Mpa-0.6Mpa, and the laminating roller includes an upper roller and a lower roller, the upper roller is a PU roller with a Shore A of 85-90 degrees, the center height of the upper roller is 0.2-0.3mm, and the lower roller is a hollow oil-warmed roller, and the oil temperature of the lower roller is 75±2°C.

9. The processing method according to claim 8, characterized in that: The method further includes step S400': rolling the silver stone paper with the transfer film into a roll, and curing it at a first preset temperature for 48-72 hours, wherein the rolling tension is 20±2KG and the first preset temperature is 45-55°C.

10. A silver stone paper, characterized in that, The silver stone paper is made according to the processing method according to any one of claims 1 to 9.